Early radiological intervention and haematology screening is associated with excellent outcomes in Budd–Chiari syndrome. Issue 12 (10th December 2017) - Mo, Allison; Testro, Adam; French, Janine; Robertson, Marcus; Angus, Peter; Grigg, Andrew
Abstract: Background: Budd–Chiari syndrome (BCS) is a rare and life‐threatening disorder, resulting from thrombosis of the hepatic veins. Various treatments, including pharmacological, radiological and surgical interventions, have been used. Aim: To describe retrospectively our institution's experience with management of patients with BCS. Methods: A retrospective study of all cases of primary Budd–Chiari syndrome presenting to our institution between January 2000 and August 2012 was performed. Patients with secondary Budd–Chiari syndrome due to malignancy or local mass compression were excluded. Results: Between 2000 and 2012, 27 patients with primary BCS presented with a median Rotterdam score of 1.16 (range: 0.07–2.11). A total of 24 patients (89%) had at least one risk factor, with the commonest being myeloproliferative neoplasm (MPN), detected in 17 of 24 (71%) of the tested patients, including four patients with normal blood counts at diagnosis. All patients were anticoagulated with warfarin or low‐molecular‐weight heparin (LMWH). A total of 25 (92.6%) patients also had primary radiological interventions, consisting of transjugular intrahepatic portosystemic shunt (TIPS) in 18 (67%) patients and/or angioplasty/stenting in 11 (40%). A total of 14 patients developed TIPS stenoses, requiring a median of 1.5 (range: 1–14) revisions. No patient developed TIPS failure requiring alternative therapy. Two patients were lost to follow‐up. At a median follow up of 59 months (range: 2–248 months), the overall survival was 96% at 1 year and 81% at 5 years, much greater than predicted by the Rotterdam score. No patients required liver transplantation. Conclusion: There is a high incidence of MPN in patients with primary BCS, including patients with normal peripheral blood counts at the time of diagnosis. Our approach of anticoagulation, aggressive and early radiological intervention aimed at rapid decompression of the congested liver resulted in excellent medium‐term outcomes.